2010
DOI: 10.1007/s10803-010-1110-z
|View full text |Cite
|
Sign up to set email alerts
|

Associating Neural Alterations and Genotype in Autism and Fragile X Syndrome: Incorporating Perceptual Phenotypes in Causal Modeling

Abstract: We have previously described (see companion paper, this issue) the utility of using perceptual signatures for defining and dissociating condition-specific neural functioning underlying early visual processes in autism and FXS. These perceptually-driven hypotheses are based on differential performance evidenced only at the earliest stages of visual information processing, mediated by local neural network functioning. In this paper, we first review how most large-scale neural models are unable to address atypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
4
11
0
Order By: Relevance
“…These results are most consistent with local neural models of autistic perception5643 that emphasize atypical extraction of elementary visual information by neural systems operating within early sensory brain areas474849. Such models are most consistent with ASD's perceptual phenotype being defined by the altered activity of early visual mechanisms, rather than the collateral consequence of a reduced global representation of non-social or social information.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results are most consistent with local neural models of autistic perception5643 that emphasize atypical extraction of elementary visual information by neural systems operating within early sensory brain areas474849. Such models are most consistent with ASD's perceptual phenotype being defined by the altered activity of early visual mechanisms, rather than the collateral consequence of a reduced global representation of non-social or social information.…”
Section: Discussionsupporting
confidence: 77%
“…This supports the hypothesis that GABAergic mechanisms play an important role in sensory discrimination. An alteration of these specific mechanisms may be responsible for increased sensitivity to high-spatial frequency information in ASD43, and possibly, in other sensory modalities where GABAergic transmission is involved in shaping the response properties of perceptual mechanisms (i.e., auditory cortex).…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies have shown that GABA mediates this balance in both visual and auditory modalities [61][63]. The implication of altered lateral GABAergic inhibition in perceptual anomalies in autism is consistent with behavioural, physiological and genetic demonstrations of altered lateral inhibition within early visual areas in autism [56], [64], [65]. There is also evidence that high concentrations of GABA in humans are related to enhanced line orientation [61] and tactile discrimination thresholds [66], supporting the hypothesis that GABAergic mechanisms play an important role in cross-modal alteration of perception in autism.…”
Section: Discussionsupporting
confidence: 66%
“…We propose to label this factor the p -factor, to distinguish it from the g -factor. Such an altered perceptual factor in autism is likely to underlie and generate cascade effects on several cognitive and adaptive mechanisms [56], [57], including, but not limited to, various perceptual abilities across modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Of the individuals who are diagnosed with autism and FXS, impairment in social interaction is prominent [27] and these individuals function at significantly lower levels of development with a decreased growth rate [28]. The relatively high frequency of autism in FXS may eventually provide clues into the genetic pathogenesis of some forms of idiopathic autism [29]. …”
Section: Psychiatric Manifestationsmentioning
confidence: 99%